Love, utterances and their justification - Suarez-Rivero, David (2025)
In this paper, I offer a justification scheme that provides criteria to support the use of romantic love utterances, both in the contexts of long-distance relationships, aided by electronic media as a consequence of the SARS-CoV-2, as well as in the context of face-to-face relationships. I show how these utterances are not referential, they are not justified by feelings or sentiments. They are justified by physical records, a personal story, a shared story and a plan for the future. I conclude that these last four elements must be satisfied to be supported in the use of such utterances.